The Classroom Physical Space as a Learning Ecosystem - Bridging Approaches: Results from a Web Survey - Sardinha, Lara (2018)
The classroom physical space enfolds several dimensions such as the social, cultural, architectural and technological. The current scenario of digitally equipped classrooms in which new pedagogical approaches based on collaborative learning, project-based learning and personalized learning are being used, call for the need to rethink the classroom physical space. Despite of the existence of some new classroom physical spaces aiming to answer this new reality, like the Future Classroom Lab, we argue that there might be lacking an innovative interior design strategy encompassing these aspects and fulfilling all the classroom physical space dimensions. Thus, this paper aims to present the perspective the authors have concerning the classroom physical space as a learning ecosystem and to start building the bridges between different approaches to space and relating them to the classroom physical space, in order to create an innovative interior design strategy that will improve the use of classroom physical space in its different dimensions. We also present the first results of an European web survey applied to the European Schoolnet Future Classroom network members that aimed at understanding how their spaces were thought and how they are being perceived; a brief discussion of the results, which, overall, are positive, is also presented. The paper ends with some references to the future work.